The use of discriminant analysis in the assessment of the municipal company’s financial health - Yakymova, Larysa; Kuz, Vasyl (Centre of Sociological Research, 2019)
Decentralization processes in CEE countries have stimulated the search for measures of financial health of municipal companies that would be comparable and understandable to a broad range of stakeholders. In this study, we developed a five-factor discriminant model for assessing the municipal company’s financial health (M-Score model) using data from 50 Ukrainian companies for 2014-2017. The final test sample consisted of 71 companies operating in Bulgaria, Croatia, the Czech Republic, Poland, Romania and Ukraine. Our findings can be summarized as follows. First, the empirical model suggests that the equity-assets ratio, the current ratio, and the average accounts receivable turnover have both the highest discriminatory power and the greatest impact on the municipal company’s financial health. Secondly, we provide convincing evidence that the municipal company’s financial health does not depend on the region, but on the nature of the activity and the purpose of enterprise activity. In particular, water and energy utilities are generally financially unhealthy, and out of 45 so-called necessary enterprises, only 12 are classified as financially healthy. The company’s M-Score will help managers, lenders, investors, local authorities, and the public to answer the following questions: Can the company avoid financial default? What is its position at the local level? What is its place in the industry?
Keywords: municipal company; financial health; multiple discriminant model; M-Score; CEE countries